Respostas
respondido por:
3
f(x) = - 3x + 6
0 = - 3x + 6
3x = 6
x = 6/3
x = 2
y = 0; x = 2
f(1) = - 3.1 + 6
f(1) = - 3 + 6
f(1) = 3
x = 1; y = 3
****************************
f(-1) = - 3.(-1) + 6
f(-1) = 3 + 6
f(-1) = 9
x = - 1; y = 9
0 = - 3x + 6
3x = 6
x = 6/3
x = 2
y = 0; x = 2
f(1) = - 3.1 + 6
f(1) = - 3 + 6
f(1) = 3
x = 1; y = 3
****************************
f(-1) = - 3.(-1) + 6
f(-1) = 3 + 6
f(-1) = 9
x = - 1; y = 9
Anexos:
Anônimo:
vou botar o gráfico....
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás